The Effectiveness Of Sports Massage On Ankle Injury Rehabilitation In East Java SMANOR Athlete - Mohamad Dimas Sasongko Putro; Ali Maksum; Endang Sri Wahjuni (UNIVERSITAS NEGERI MAKASSAR, 2023)
The purpose of this study was to find out how effective Sports massage Effriction therapy is for ankle injury rehabilitation, ankle injuries can be one of the things that bother students, but in SMANOR there are currently supporting health services such as mass services, some students who have ankle injuries they say that the handling of massage with the methods applied at UPT SMANOR JATIM still does not bring significant results, they said that they still felt pain, and in terms of range of motion still could not be moved optimally so that it affected the quality of school and the training they underwent, The design of this study used a quasi-experimental design, The subjects in this study amounted to 32 patients taken from SMANOR JATIM students who had ankle injuries with a population of 160 students. The data collection technique used is to use the Visual Analogue Scale (VAS) instrument as a way to measure pain before treatment and after treatment. It then uses a goniometer to measure the range of motion of the flexion-extension ankle before and after treatment. The data processing technique in this study uses computational calculations of the SPSS (Statistical Product and Service Solution) Version 26.0 program. Sports massage therapy is effective in improving ankle ROM. Expressed significantly seen from the value of t in the flexion movement of 14.576 mean of 8.878. In the extension movement, the t value of 19.471 is the mean of 12.324. Physiologically, the treatment of massage therapy is useful for reducing inflammation and increasing ROM. (2) Sports massage therapy is effective in reducing pain in ankle injuries. This can be stated as significant as seen from the t value of 17.676 with a mean of 5.780. Physiologically, treatment of sports massage therapy can reduce inflammation and pain in ankle injuries. This study concludes that the treatment of sports massage is effective in dealing with ankle injuries and effective in reducing pain in athletes who experience ankle injuries at SMANOR East Java.